Firm constraints on the link between proactive innovation, open innovation and firm performance - Nguyen Thanh Liem; Nguyen Vinh Khuong; Thai Hong Thuy Khanh (Journal of Open Innovation: Technology, Market, and Complexity, 2019)
This study aims to examine the impacts of firm constraints and proactive innovation on firm performance, using a sample of 3504 small and medium enterprises (SMEs) in Vietnam from 2011–2015. Our findings suggest that technological innovations in general are beneficial to firm performance, increasing firm sales and profits. Further filtering innovations into two categories of proactive and reactive ones, we find that reactive innovation negatively affects firm performance, consistent with the view that proactive entrepreneurial behavior is a highly sought-after characteristic or a valuable resource for a firm as specified in resources-based theory. Finally, our result implies that if firms have low constraint or have sufficient resources, proactive strategies should be the choice if firms seek to improve their performance.
Keywords: 650; firm performance; manufacturing industry; proactive innovation; reactive innovation; technological innovation